Outcomes of Burkitt lymphoma with bone marrow involvement or Burkitt leukemia in Chinese children. Issue 2 (18th June 2021) - Zhu, Jia; Zhen, Zijun; Wang, Juan; Sun, Feifei; Lu, Suying; Huang, Junting; Zhang, Yizhuo; Sun, Xiaofei
ABSTRACT: Importance: Burkitt lymphoma with bone marrow involvement and Burkitt leukemia behave aggressively. Thus far, there are limited data concerning survival and toxicity in Chinese children with Burkitt lymphoma or Burkitt leukemia who have undergone treatment with the non‐Hodgkin's lymphoma Berlin‐Frankfurt‐Münster‐90/95 (NHL‐BFM‐90/95) protocol. Objective: To analyze outcomes and toxicity in pediatric patients who exhibit Burkitt lymphoma with bone marrow involvement or Burkitt leukemia following treatment with the NHL‐BFM‐90/95 protocol. Methods: Patients aged <18 years with bone marrow involvement/leukemia who were treated with the NHL‐BFM‐90/95 protocol, with or without rituximab, in Sun Yat‐Sen University Cancer Center from April 2004 to December 2018 were included in this retrospective analysis. Results: Twenty‐five patients were eligible. Burkitt lymphoma with bone marrow involvement and Burkitt leukemia were present in 10 and 15 patients, respectively. Central nervous system infiltration was not observed in any patients. All patients underwent chemotherapy involving NHL‐BFM‐90/95 protocol. Six courses of treatment were administered to each patient (v‐AA‐BB‐CC‐AA‐BB‐CC). The BFM‐90/95 plus rituximab protocol was administered to 13 patients. The median follow‐up interval was 31.9 months (range, 2.5–158 months). Of the 25 patients, four died: three died of tumor progression and one died of therapy abandonment after relief of tumor lysis syndrome. The estimated 5‐year event‐free survival and overall survival rates were both 85.8% ± 5.0%. Interpretation: Chinese pediatric patients who exhibit Burkitt lymphoma with bone marrow involvement or Burkitt leukemia can achieve optimal treatment outcomes and exhibit good tolerance when using the NHL‐BFM‐90/95 protocol.